Entre dois mundos: os monastérios irlandeses como espaços de liminaridade histórica e o papel dos santos nesses espaços-tempo de transição - Boulhosa, Tatiana Machado (2015)
The fourth, fifth and sixth centuries are known, in the History of the Celtic-speaking countries as the Age of Saints . Throughout these three hundred years or so, Christianity went from a relatively unknown religion to the main form of adoration in Ireland, Scotland, England and Wales. First, there were missionaries from the continent, and then there were monks and monasteries in the islands. Later, there were missionaries from the islands and monasteries in the continent. When these missionaries arrived, they brought with them the Gospel as it was preached and lived in Rome; when they departed, they were preaching like the Celts, living like the Celts and believing like the Celts. For a while, it seemed like there would be two Churches. Then the world changed: the Middle Ages arrived and the Celts were Romanized. However, some of what they preached, lived and believed came thru, modified, adapted and ready to face whatever challenges this new world might impose them. That is the reason why this dissertation aims at showing how was it that Celtic-speaking people lived before Christianity, how were them converted, how did they comprehend Christianity and what happened after that. In order to do that, the text articulates itself around the image of some of the most important founders of monasteries, men who later became saints: Patricius, Columba and Columbanus. Moreover, its main goal is to show that, during the time frame in question, Celtic monasteries functioned not only as an expression of faith or religion as an institution but also a geographical space of historical liminarity; the very essence of time-space transition